Dinamika Spiritualitas Mahasiswa: Analisis Konsistensi Ibadah Mahasiswa Kimia UPI di Tengah Tekanan Akademik - Muhammad Dian Pratama Putra; Muhammad Nadhif Azmi Ubaidillah; Tanti Nurizki; Usup Romli (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2026)
This study aims to conduct a comprehensive analysis of the worship consistency patterns among Chemistry and Chemistry Education students at FPMIPA UPI amidst intensive academic pressure. Using a descriptive quantitative method via a survey of 35 respondents, this study evaluates the dynamics between heavy science curricula and spiritual stability. The results indicate that the level of academic pressure is perceived as very high by the majority of students (83.8%), driven by high achievement expectations and dense laboratory schedules that significantly complicate time management (81.1%). Key findings reveal a contrast in religious behavior; mandatory worship remains stable, with 70.3% of respondents performing prayers on time as a result of the internalization of Islamic values. Conversely, sunnah (voluntary) worship becomes the most vulnerable dimension to be neglected (59.5%) due to physical exhaustion and the psychological impacts of campus activities. Nevertheless, 94.6% of respondents acknowledge that worship provides a sense of calm, confirming the role of prayer as mental stabilization to prevent academic depression according to Buya Hamka's perspective. The study concludes that spiritual orientation serves as the most effective spiritual coping mechanism in exact science environments. Therefore, as a practical solution, strategic interventions through Islamic Guidance and Counseling (Bimbingan Konseling Islam/BKI) services are recommended, focusing on Islamic time management training, strengthening academic resilience, and utilizing worship-reminder technology to maintain the balance between study demands and overall spiritual practice quality.